RNA interference (RNAi) applications to the management of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae): Its current trends and future prospects - Kebede, Megersa; Fite, Tarekegn (Frontiers in Molecular Biosciences, 2022)
The fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) is among the invasive insect pests that damages maize and sorghum, the high-priority crops in newly colonized agro-ecologies, including African contexts. Owing to the increasing infestation of the pest and the limitations of current conventional methods for its management, there is a call for discovering advanced pest management approaches. RNA interference (RNAi) is an emerging molecular tool showing pliable potential for the management of S. frugiperda. We conducted a search of the recent application of RNAi literature using Google Scholar and Mendeley to find advanced paper in S. frugiperda managements using RNAi molecular tools which led to growth inhibition, developmental aberrations, reduced fecundity, and mortality, mainly by disruption of normal biological processes of the pest. Although efforts have been made to accelerate the utility of RNAi, many factors limit the efficiency of RNAi to achieve successful control over S. frugiperda. Owing to RNAi's potential bioactivity and economic and ecological acceptability, continued research efforts should focus on improving its broad applicability, including field conditions. Screening and identification of key target genes should be a priority task to achieve effective and sustainable management of these insects via RNAi, an emerging molecular tool. In addition, a clear understanding of the present status of RNAi utilization in S. frugiperda management is of paramount importance to improve its efficiency. Therefore, in this review, we highlight the biology of S. frugiperda and the RNAi mechanism as a foundation for the molecular management of the pest. Then, we discuss the current knowledge of the RNAi approach in S. frugiperda management and the factors affecting the efficiency of RNAi application. Last, the prospects for RNAi-based insect pest management are highlighted for future research to achieve effective management of S. frugiperda.